KESEJAHTERAAN DAN EMOSI KARYAWAN DI TEMPAT KERJA - Angga Guriang Gautama Putra; Muh Fitrah Ramadhan Umar; Cholicul Hadi (Universitas Negeri Makassar, 2019)
Levels of wellbeing, financial factors, emotional and psychological factors need to be addressed to individuals in the workplace. Individual well-being is met is expected to occur individual satisfaction in the workplace. Individual satisfaction, groups in the workplace have an impact on emotions. This study aims to examine the role of welfare in individual emotions. The method used in this research is observation, interview and secondary data. The sample in this research is cleaning service of Faculty of Psychology Airlangga University Surabaya, random sampling method. The result of this study is that employees have good emotions and well-being when they are at work. The most important factor why they can enjoy the job is the existence of a conducive, comfortable, and familial work environment. In this research, the conducive working environment factor is quite dominant. In addition, the relatively small working pressures and awareness of the difficulty of finding employment are also factors why these employees decide to survive.